THE STUDENTS’ LEARNING TRAJECTORY IN GEOMETRY CONCEPT BY USING LOCAL INSTRUCTION THEORY BASED ON REALISTIC MATHEMATICS EDUCATION APPROACH - Nasriadi, Ahmad; Sari, Intan Kemala; Salmina, Mik; Fitriati, Fitriati; Muzakir, Ully; Fajri, Nurul; Fitra, Rahmat; Rahmattullah, Rahmattullah (Jurnal Ilmiah Teunuleh, 2022)
Abstract. This study aims to find out how learning trajectory is right for students in understanding the concept of geometry. Learning the area of triangles and quadrilateral areas through trivial problems may be easy for students, but not in the context of complex problems. Therefore, through learning with Realistic Mathematics Education (RME) approach is known learning trajectory that can help students learn geometry. From the results of the study showed that through the provision of problems that are situational and close to the experience of students give the impact of desire and motivation and challenge students to solve problems. From this experience, students realize or do not start building material concepts that should be obtained in learning mathematics. This is a suggestion that the teaching and learning process should present problems that can take advantage of the student's previous experience before it becomes a new formal concept.